EVALUASI KONDISI FISIK (PENYEDIAAN DAN PENGGUNAAN) PRASARANA DAN SARANA UNTUK MENDUKUNG MODA TRANSPORTASI UMUM DI KOTA TANGERANG (KORIDOR 2) - Sena Wiratama; Regina Suryadjaja (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2023)
Indonesia has a land area of 1,922,570 km2 and has 38 provinces and has 415 districts, 1 administrative district, 93 cities, and 5 administrative cities where a mode of public transportation is needed to facilitate people's mobility in carrying out daily activities. The Indonesian government, through the ministry of transportation, always makes improvements in the field of public transportation modes so that the Indonesian people can feel safe and comfortable in using public transportation modes, one of which is BRT (Bus Rapid Transit). One of them is Tangerang City, which is in Banten Province with an area of 164.55 km2. The city of Tangerang has provided a mode of public transportation in the form of a rapid transit bus or commonly called Tangerang Ayo (TAYO) which has a price or fare that is quite cheap, besides TAYO is made to reduce the number of congestion at several points in the City of Tangerang, Trans Kota Tangerang is the Bus Rapid Transit transportation system which began operating on December 1, 2016 in the City of Tangerang, Banten. Therefore, the purpose of this research was to find out how the public perceives the existence of the BRT mode of transportation (corridor 2) in terms of aspects of infrastructure and operational support facilities. This research is based on descriptive research through qualitative and quantitative approaches. Qualitative data collection was obtained by way of direct surveys to the field and by using a questionnaire. The results of the study showed that BRT supporting infrastructure (corridor 2) was still below the standards set by the ministry of transportation and was also confirmed by data on the perceptions of service users of the Tangera Ayo BRT (corridor 2). Keywords:  Bus Rapid Transit (BRT); public transportation; user Abstrak Pemerintah Indonesia mwlalui kementerian transportasi selalu melakukan pembenahan dalam bidang moda trasnportasi umum agar masyarakat Indonesia bisa merasakan keamanan dan kenyaman dalam penggunaan moda transportasi umum seperti salah satunya iyalah BRT (Bus Rapit Transit). Salah satunya Kota Tangerang yang berada di Provinsi Banten dengan luas wilayah 164,55 km2,kota Tangerang telah menyediakan moda transportasi umum berupa bus rapid transit atau biasa disebut Tangerang Ayo (TAYO) yang memiliki harga atau ongkos yang cukup murah selain TAYO ini dibuat untuk menekan jumlah kemacetan di beberapa titik yang berada di Kota Tangerang, Trans Kota Tangerang adalah sistem transportasi Bus Rapid Transit yang mulai beroperasi pada tanggal 1 Desember 2016 di Kota Tangerang Banten. Maka dari itu tujuan dibuatnya penelitian ini dibuat untuk mengetahui bagaimana persepsi masyarakat terhadap adanya moda transportasi BRT (koridor 2) dari segi aspek prasarana dan sarana penunjang operasionalnya. Penelitian ini berbasis penelitian deskriptif melalui pendekatan kualitatif dan kuantitatif. Pengumpulan data kualitatif didapatkan dengan cara survey langsung ke lapangan serta dengan menggunakan kuesioner. Hasil penelitian didapatkan bawah prasarana penunjang BRT (koridor 2) masih di bawah standar dari kementerian perhubungan dan juga terkomfirmasi dengan data persepsi pengguna jasa BRT Tangera Ayo (koridor 2).